First fossil pseudopsine rove beetle from mid-Cretaceous Burmese amber (Coleoptera: Staphylinidae: Pseudopsinae) - Liu, Yuchu; Tihelka, Erik; Tian, Li; Huang, Diying; Cai, Chenyang (Zootaxa, 2020)
Pseudopsinae represented by four genera with just over 50 species in the Recent fauna represent one of the smallest subfamilies of the megadiverse family Staphylinidae. Here we describe the first fossil member of the subfamily Pseudopsinae. Cretopseudopsis maweii gen. et sp. nov. preserved in mid-Cretaceous Burmese amber (ca. 99 Ma) is distinguished from extant pseudopsine genera by head not carinate, apical maxillary palpomere only slightly narrower than penultimate segment, subocular carinae absent, temples short, pronotal lateral margin smoothly rounded, and mesocoxae separated by an elongate process of the mesoventrite. Our discovery of Cretopseudopsis gen. et sp. nov. provides evidence that the subfamily Pseudopsinae originated by the Albian–Cenomanian and suggests a Gondwanan distribution of the group in the Cretaceous.